Distribution of a model biocontrol agent (Serenade® MAX) in apple and pear by mason bees and bumble bees. (8th July 2020) - Maebe, Kevin; Vanderhaegen, Ruben; Pisman, Matti; Eeraerts, Maxime; Cottyn, Bart; Vanhoutte, Bart; Smagghe, Guy
Abstract: Biocontrol agents (BCAs) are commonly sprayed on flowering pipfruit trees to prevent them from getting infected by various pathogens. By entomovectoring, BCAs can be directly delivered onto the flowers. However, we currently lack knowledge on the distribution dynamics of BCAs by pollinators. Here, managed bees, both bumble bees ( Bombus terrestris ) and mason bees ( Osmia bicornis and Osmia cornuta ), were placed in the vicinity of flowering pipfruit trees (pear ‐'Conference', and apple—'Svatava' and 'Jonagold'), and this allowed us to investigate the distribution of a model BCA, namely, Serenade® MAX, from spray‐inoculated flowers of a centralized tree to non‐inoculated flowers of surrounding receiver trees by bees in an experimental setup in outdoor conditions. One hour after inoculation, we detected an enrichment of BCA in the flowers of the receiver trees and this for each tested pipfruit. The distribution of BCA from treated to untreated flowers was homogenous between the receiver trees for 'Svatava', while significantly different loads were detected for both 'Conference' and 'Jonagold', which might be due to differences in environmental factors, and/or bee characteristics. More research is needed to understand the distribution dynamics of BCAs by pollinators in field conditions, such as in commercial orchards or crop fields, and how this could result in an efficient control. Abstract : The secondary distribution of a model biocontrol agent (BCA) by managed bees, bumble bees ( Bombus terrestris ) and mason bees ( Osmia spp.), from spray‐inoculated flowers of a centralized tree to the noninoculated flowers of surrounding receiver trees was investigated in an experimental setup in outdoor conditions using flowering pipfruit trees (pear ‐'Conference', and apple—'Svatava' and 'Jonagold'). For each tested pipfruit, an enrichment of BCA was detected in the flowers of the receiver trees, and this 1 h after inoculation. Although a homogenous distribution of BCA was detected between the receiver trees for 'Svatava', significantly different loads were detected for both 'Conference' and 'Jonagold', possibly due to differences in environmental factors, and/or bee characteristics.